Which is the best environment for the development of the early life stages of fish during the dry season? - Esguícero,André Luiz Henríques (2010)
AIM: The main objective of this study was to investigate the quality of habitats for early life stages of fish in the Jacaré-Guaçu River, during the dry phase; METHODS: For assessing the quality of the habitats for the development of early life stages, the relative condition factor was applied to the juveniles of five species of fishes, captured in four different habitats (reservoir, floodplain lake, main river, and tributary). The juveniles were caught in macrophytes of the littoral zone by a rectangular sieve, in the dry season of 2008 and 2009; RESULTS: The species Astyanax altiparanae thrived similarly in the four habitats, and A. fasciatus, Hyphessobrycon eques, Hoplias malabaricus and Serrapinnus notomelas, showed higher values of relative condition factors in the reservoir and in the lake. Among the species, A. fasciatus showed the highest values of the relative condition factor in these two habitats; CONCLUSIONS: It is likely that the complexity of the macrophytes' stands and the current velocity were the main factors influencing the development of juveniles. It was found that a lower current velocity can propitiated the establishment of a greater richness of macrophytes, which in turn can influence positively the development of fish juveniles. Moreover, a higher current velocity ends in a higher energy demand for swimming.